Fostering Programming Logic Skills in High School Students Through Project-Based Learning: An Educational Experience - Galeno, Larissa; Costa, Luis Felipe; Xexéo, Geraldo (Anais do Simpósio Brasileiro de Educação em Computação (EDUCOMP), 2024)
In recent years, the burgeoning demand for skilled professionals in the technology sector has become increasingly evident. Capitalizing on this trend, a non-governmental organization in Rio de Janeiro recognized it as a unique opportunity to empower the city's youth. In collaboration with a public university, it was proposed a training program focused on programming logic with Python and an introduction to data analysis, specifically tailored for high school students. Thus, this work aims to present the experience of designing and implementing this course. With a clear emphasis on the unique characteristics of our target audience, we crafted a curriculum utilizing active teaching methodologies: project-based learning and the flipped classroom approach. By the conclusion of the course, students not only demonstrated their ability to complete the proposed projects but also actively participated in an evaluation of their learning experience, answering a questionnaire and participating in interviews. The results of this evaluation were overwhelmingly positive, shedding light on the student's desire to pursue further studies in computer science.